2017
DOI: 10.4314/ijbcs.v11i3.6
|View full text |Cite
|
Sign up to set email alerts
|

Effets strongylicides <i>in vitro</i> de l’extrait aqueux de feuilles de <i>Ficus exasperata</i> Valh. 1805 (Moraceae)

Abstract: REMERCIEMENTS Les auteurs remercient le Ministère de l'Enseignement Supérieur et de la Recherche Scientifique du Benin pour son appui financier sous forme de bourses doctorales.RESUME L'usage massif et abusif de composés chimiques dans la lutte contre les parasitoses animales a montré ses limites tant sur le plan efficacité (échecs consécutifs au phénomène de résistances) que sur le plan écologique (écotoxicité des molécules). Les recettes ethno-vétérinaires, qui se fondent sur l'exploitation de la riche flore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
2
3
1
Order By: Relevance
“…Quanti cation of the secondary metabolites responsible for the medicinal plant properties in aqueous extracts of E. hirta shows a wide range of levels of total polyphenols, total avonoids and condensed tannins. In contrast to our present study, numerous studies have qualitatively shown the presence of these secondary metabolites within different plant extracts (Wadré et al, 2015;Houngnimassoun et al, 2017). However, Azando et al (2022) obtained a slightly higher condensed tannin content in Newbouldia laewis and Zanthoxylum zanthoxyloides extracts compared to our present study.…”
Section: Discussioncontrasting
confidence: 99%
“…Quanti cation of the secondary metabolites responsible for the medicinal plant properties in aqueous extracts of E. hirta shows a wide range of levels of total polyphenols, total avonoids and condensed tannins. In contrast to our present study, numerous studies have qualitatively shown the presence of these secondary metabolites within different plant extracts (Wadré et al, 2015;Houngnimassoun et al, 2017). However, Azando et al (2022) obtained a slightly higher condensed tannin content in Newbouldia laewis and Zanthoxylum zanthoxyloides extracts compared to our present study.…”
Section: Discussioncontrasting
confidence: 99%
“…HEM is more efficient on eggs and Haemonchus contortus adult worms compared to others with IC 50 of 0.457 mg/mL and LC 50 of 1.329 mg/mL, respectively. Our results are comparable to those obtained by Houngnimassoun et al [23], which is 100% from 64 mg/mL of Ficus exasperata, and those obtained by Belemlilga et al, who showed that the extract of Saba senegalensis gave a 97% hatch inhibition rate with 15 mg/mL [31].…”
Section: Discussionsupporting
confidence: 91%
“…These include: Balanites aegyptiaca [17], Saba senegalensis [18], Cassia sieberiana, Guiera senegalensis and Excoecaria grahamii [19], Securidaca longepedunculata [20]. For more efficiency in improving the health of small ruminants, it would be wise to conduct studies on forage plants for their nutritional values and also for their richness in specific secondary metabolites such as tannins, flavonoids, saponins and alkaloids, whose anthelmintic properties and effects on zootechnical performance are known [21] [22] [23]. Burkinabe traditional medicine has several medicinal plants used by the population to treat gastrointestinal parasitosis.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality Rate (%) : Difference between columns, p-value : Comparison between concentration. study, numerous studies have qualitatively shown the presence of these secondary metabolites within different plant extracts [17,18]. Phytochemical screening studies carried out in Niger, Senegal and Côte d'Ivoire showed the presence of these various secondary metabolites in various E. hirta extracts, similar to our present study [19][20][21].…”
Section: Dosesupporting
confidence: 89%